Historical development of talent identification and development initiatives in Japan - Kinugasa, T.; Fujiwara, A.; Waku, T.; Gulbin, J. (Sports Science in Elite Athlete Support, 2018)
Talent identification & development (TID) has been positioned as an important measure of sport policy from the viewpoint of high performance sport. TID at the national level has been evolving in various countries including United Kingdom (UK) and Australia. Japan Sport Council (JSC) currently supports three TID models throughout the entire country: multi-sports, target sports, and transfer sports. A local TID (LTID) project on the multi-sports model was first introduced in Fukuoka prefecture in 2004. After 13 years, the LTID project has been expanded to 26 prefectures. The Japanese National TID (NTID) programme was strategically implemented by JSC in 2012 as a new national project. NTID provides opportunities and choices toward talented local athletes to create various Olympic and Paralympic pathways for potential medallists. Many countries establishing sustainable athlete development pathways highlight the need to continue being innovative and evidence-based in the approach to ensure that Japan stays at the front of this rapidly evolving field in high performance sport.